Biotelemetric Monitoring of Brain Neurochemistry in Conscious Rats Using Microsensors and Biosensors - Maria S. Desole; Robert D. O’Neill; John P. Lowry; Vittorio Mazzarello; Gianfranco Bazzu; Ylenia Spissu; Giulia Puggioni; Rossana Migheli; Gaia Rocchitta; Giammario Calia; Pier A. Serra (Sensors, 2009)
In this study we present the real-time monitoring of three key brain neurochemical species in conscious rats using implantable amperometric electrodes interfaced to a biotelemetric device. The new system, derived from a previous design, was coupled with carbon-based microsensors and a platinum-based biosensor for the detection of ascorbic acid (AA), O2 and glucose in the striatum of untethered, freely-moving rats. The miniaturized device consisted of a single-supply sensor driver, a current-to-voltage converter, a microcontroller and a miniaturized data transmitter. The redox currents were digitized to digital values by means of an analog-to-digital converter integrated in a peripheral interface controller (PIC), and sent to a personal computer by means of a miniaturized AM transmitter. The electronics were calibrated and tested in vitro under different experimental conditions and exhibited high stability, low power consumption and good linear response in the nanoampere current range. The in-vivo results confirmed previously published observations on striatal AA, oxygen and glucose dynamics recorded in tethered rats. This approach, based on simple and inexpensive components, could be used as a rapid and reliable model for studying the effects of different drugs on brain neurochemical systems